ABILITY OF SOME FUNGI TO BIOGEGRADE CARBENDAZIM FUNGICIDE - & et al, Raheem (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was amid to  isolate  soil fungi from agriculture soil and study  their roles in the biodegradation of carbendazim fungicide at different concentrations were explored for two periods of incubation. Results showed the highest degradation rates of carbendazim at 4 part per million (ppm) concentration were observed by using single culture of Aspergillus niger (69.66% and 99.96% after 10 and 20 days, respectively).In the mixed cultures of Exerohilum sp., Fusarium sp., and A. niger, the maximum degradation rate (98.34%) was achieved at the same concentration after 10 days. The mixed culture of Exerohilum sp. and Fusarium sp. demonstrated the highest degradation rates of (92.14% and 55.74%) at 8 and 12 ppm concentrations, respectively, after 10 days of incubation.